Clickbait and its influence on news structure changes in Peru - Peña Salas, Juan Pablo (2020)
The use of clickbait headlines has become common in journalism, combining marketing strategies to capture the attention of potential readers, such as the use of question marks or appealing to doubt or emotions to achieve its goal. This research work seeks to understand how the clickbait, as a resource of digital journalism, has altered traditional hierarchical criteria, instead of using structures such as the inverted pyramid. As a methodology, the digital platform of two media, one of the radio press and the other of the television press, was analyzed to identify how they used clickbait and the type of hierarchical order, as well as their characteristics, such as the use of quotes and the section.